Epidemiological Study of Malaria Infection among Pregnant Women in Gombe, Gombe State, Nigeria - W. Pindar; G. Chessed; J. M. Manu (Journal of Applied Sciences and Environmental Management, 2023)
Malaria is one of the most devastating diseases plaguing mankind. The disease is endemic in tropical and sub-Saharan Africa of which Nigeria belongs. The Epidemiological study of malaria infection among pregnant women was carried out on 1,521 patients reporting for their first antenatal clinic in hospitals and clinics, in Gombe, Gombe State, Nigeria. Giemsa stained thick and thin films for malaria parasite test was carried out on the women, alongside obtaining information on their socio-demographic characteristics. Most of our participant were in the age group 21-30 years (56.34%), while most of them had their secondary education (49.85%) and were housewives 99.41%. The prevalence of malaria was 8.48%, with the 21-30 year old age group having the highest prevalence of malaria (56.34%). The highest prevalence of malaria was among those in their second trimester (11.48%), while those with more than seven children had the highest prevalence of malaria (25.00%). The highest prevalence of malaria was seen among those with non-formal education (11.30%), housewives (8.44%) and the single pregnant women (22.22%). The prevalence of malaria was statistically significant with age group and occupation.  We advise that measures encouraging personal and environmental hygiene, use of prophylactic drugs and sleeping under treated mosquito nets should be encouraged to reduce the prevalence of malaria among the pregnant women.